Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T16:28:24+01:00
A)
3x-9
5y+5z
12x-4y
12a-3c
-14n+8n

b)
2z+1
-2b+1
0,2x-y
a+3

Mam nadzieję,że dobrze wszystko ;)
Może dostanę naj ??
2010-02-23T16:28:57+01:00
A) 3(x-3) = 3x - 9
b) 5(y+z) = 5y + 5z
c) 4(3x-y) = 12x - 4y
d) 3(4a-c) = 12a - 3c
e) -2(7-4)n = -2 * 3 * n = -6n
f) ½(4z+2) = 2z + 1
g) -⅓(6b-3) = -2b + 1
h) 0,2(x-5y) = 0,2x - y
i) 3(⅓a+1) = a + 3
2010-02-23T16:31:43+01:00
A)
3(x-3) = 3x - 9
5(y+z) = 5y + 5z
4(3x-y) = 12x - 4y
3(4a-c) = 12a - 3c
-2(7-4)n = -2 * 3 * n = -6n
b)
½(4z+2) = 2z +1
-⅓(6b-3) = -2b + 1
0,2(x-5y) = 0,2x - y
3(⅓a+1) = a + 3